A Good Samaritan - Andrews, Mary Raymond Shipman, 1860-1936; Harding, Charlotte, 1873-1951 (Salt Lake City, UT : Project Gutenberg, 2005)
"A Good Samaritan" by Mary Raymond Shipman Andrews is a fictional narrative written during the early 20th century. This story explores themes of friendship, responsibility, and the social struggles of young men navigating the complexities of life in urban America. The tale revolves around the choices individuals make when confronted with moral dilemmas, showcasing the virtues of compassion and self-sacrifice. The plot centers on Reginald "Rex" Fairfax, a theological student on the brink of an important career opportunity, who finds himself inadvertently taking care of his drunken companion, Billy Strong, instead of attending a crucial dinner meeting with an influential church figure. As Rex struggles to navigate the chaos brought on by Billy's intoxication, he faces a series of humorous yet poignant challenges. Ultimately, Rex's decision to prioritize friendship over personal ambition leads him to a deeper understanding of himself and the value of true character. The story closes with a redemptive turn, highlighting the unexpected rewards that come from being a "good Samaritan." (This is an automatically generated summary.)
Release date is 2005-05-26
E-text prepared by Juliet Sutherland, Bruce Albrecht, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: New York (N.Y.) -- Social life and customs -- Fiction